(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the clinical manifestations of patients with mosquitoes-borne diseases Study Design: Cross Section Study Place and Duration of Study: This study was conducted at the Department of Medicine, Al-Tibri Medical Hospital, Isra University Karachi Campus from April 2022 to October 2022. Materials and Methods: Study protocol was written and approval was taken from IREC, Total 100 numbers of patients with both genders were selected from Medicine OPD of Al-Tibri Hospital and were briefed about the study; written informed consents were taken. Diagnosed cases of malaria, dengue and dual dengue and malaria infection confirmed by serological analysis, patients with age of >18 and above were included in the study. Patients with negative serological markers and <18 years of age excluded from the study. Patient data was collected. Proforma was used for recording data and SPSS version 22 was used for data analysis. Results: Total 100 numbers of patients the 57 were male and 43 were females. Mean age was 35.56 ± 1.23. Out of 100 patients 44% were in Group A, and 38% were included in Group B and 18% patients were included in group C as a diagnosed with both malaria and dengue Conclusion: According to the study, the symptoms related to mosquitoes-borne diseases in all groups like fever, chills, vomiting, and conjunctivitis were reported. The percentage of severity in symptoms was recorded in Malaria and dengue patients as compare with dual infection. Low level of hemoglobulin and low platelet count were reported in all groups. Most of the symptoms and changes in hematological parameters were recorded in Malaria patients. In accordance with the results, mosquitoes-borne diseases need proper investigation and line of treatment along with preventive measures should be taken by Health care providers and ministry.